The Effect of Nutritional Support on the Disease Progression and Survival in Pediatric Patients with Solid Tumors. (2nd January 2022) - Gallo, Nora; Czuppon, Krisztina; Tomsits, Erika; Garami, Miklos; Hauser, Peter; Jakab, Zsuzsanna; Nagy, Krisztina; Kovacs, Gabor T.
Abstract: Cancer is one of the leading causes of death for children; however, appropriate nutritional status can positively affect survival. The aim of this study was to determine to what extent malnutrition risk screening and intensified nutrition support, provided by a professional team, promoted disease progression and survival in pediatric patients with solid tumors. 145 pediatric cancer patients (average age 6.3 ± 5.6 and 6.7 ± 5.4 years) with solid tumors undergoing chemotherapy participated in the study. Two 3-year periods were studied: 2009-2011 and 2012-2014. Patient characteristics and treatment protocols were identical, but in Period 2, with the foundation of our nutrition support team malnutrition risk screening was made mandatory upon every hospital admission. As a result of intensified nutrition support the time from diagnosis to completion of treatment (802 vs. 512 day, p < 0.001) and the need for antimycotic treatment reduced significantly (47.8% vs. 29.1%, p = 0.036). The total percentage of surviving children was 60.3% and 75.0% in Period 1 and 2 respectively. Decrease in weight-for-height percentile during treatment and central nervous system tumors are significant predictors of a less favorable survival. Malnutrition risk screening and intensified nutrition therapy have positive effects on nutritional status and therefore patient survival in pediatric cancer patients.